Creator and creation according to Calvin on Genesis - Earnshaw, Rebekah (Reformed historical theology, 2020)
Cover -- Title page -- Copyright -- Table of contents -- Body -- Acknowledgements -- Abbreviations -- A note on translations and sources -- 1. In the Beginning -- 1.1 Creation and Genesis -- 1.2 Calvin on Genesis -- 1.3 Calvin and Creation -- 1.4 Biblical Theologian -- 1.5 Piety and the Usefulness of Scripture -- 1.6 Creator, Act of Creation, Creatures, and Providence -- 2. Creator -- 2.1 And -- 2.2 Knowledge of God the Creator -- 2.3 God the Creator -- 2.3.1 L'Eternal -- 2.3.2 Infinitely Distinct -- 2.3.3 Abundantly for Creatures -- 2.3.4 Virtues -- 2.4 Calvin's Creator: Full, Engaged, and Concrete -- 3. The Agent and Act of Creation -- 3.1 A Trinitarian Account -- 3.2 Theological Cosmology -- 3.3 From Nothing -- 3.4 In and with Time -- 3.5 A Purposeful Beginning -- 4. Creatures -- 4.1 Creaturely Goodness -- 4.1.1 Beginning of Creaturely Goodness -- 4.1.2 End of Creaturely Goodness -- 4.1.3 Knowing Creaturely Goodness -- 4.2 Created Order -- 4.2.1 Invisible and Spiritual Creation -- 4.2.2 Visible Non-Animate Creation -- 4.2.3 Visible Animate Creation -- 4.3 Corruption and Disorder -- 4.3.1 Its Source -- 4.3.2 Its Total Scope -- 4.3.3 Disordered Animals and Humans -- 4.4 Use of Created Goodness, Order, Corruption, and Disorder -- 5. Providence -- 5.1 Providence and the Promise: Abraham -- 5.2 Providence, the Church, and the Wicked: Joseph -- 5.2.1 Fatherly Care for the Church -- 5.2.2 Restraining the Wicked -- 5.2.3 The Providential Agent and Means -- 5.3 Creatures under the Creator's Providential Governance -- 6. In the End -- Bibliography -- Sources and Translations -- Other Sources.